2021
DOI: 10.24843/e-jl.2021.v15.i01.p03
|View full text |Cite
|
Sign up to set email alerts
|

Ecolinguistic Approaches in Development of English Teaching Materials for English for Business

Abstract: This study aims at finding an English learning model using an ecolinguistic approach in the preparation of syllabus and teaching materials. Qualitative descriptive methods are applied and natural phenomena are used to develop syllabus. This phenomenon focuses on learning and teaching strategies that are applied. Data obtained through tests, questionnaires and direct observation for needs analysis. The syllabus was developed based on the results of material analysis and needs.The ecological approach in educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…So, overall the Ecolinguistic-based English for Computer learning tool "lexicon in the Mbojo language" for Developing Students' Creative Thinking Ability is good according to expert judgment. The results of the validation of the observation sheet on the implementation of the Ecolinguistic-based English for Computer learning tools and the student response questionnaire to the Ecolinguistic-based English for Computer learning tools were also in the correct category (Krismayani et al, 2021;Tjendani et al, 2019). According to a previous study the validity test was carried out to determine the instruments' advantages and disadvantages (Fadila, 2018).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…So, overall the Ecolinguistic-based English for Computer learning tool "lexicon in the Mbojo language" for Developing Students' Creative Thinking Ability is good according to expert judgment. The results of the validation of the observation sheet on the implementation of the Ecolinguistic-based English for Computer learning tools and the student response questionnaire to the Ecolinguistic-based English for Computer learning tools were also in the correct category (Krismayani et al, 2021;Tjendani et al, 2019). According to a previous study the validity test was carried out to determine the instruments' advantages and disadvantages (Fadila, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Another research the titled "Ecolinguistic Approaches in Development of English Teaching Materials for English for Business." This study found that the environmental system in language education has several characteristics used to find new ways to be applied in language learning (Krismayani et al, 2021). Based on the problems and results of previous research, the researcher is interested in conducting a study related to Ecolinguistic-Based English for Developing Students' Creative Thinking Abilities.…”
Section: Introductionmentioning
confidence: 99%
“…This study was designed in the form of a descriptive qualitative approach (Krismayani et al, 2021;Surono, 2018). Additionally, in this study, words and phrases were used to display and describe the results.…”
Section: Methodsmentioning
confidence: 99%
“…English, which is favored as the predominant language of communication, has six main lexical categories distinguished by their morphological properties and semantic features: noun, verb, adjective, adverb, preposition, conjunction, determiner, and exclamation (Gizatulina et al, 2020;Suwastini et al, 2023). From the extent of the study that discusses language and linguistics, this study is intended to analyze verbs in English, seeing their use as the main feature in a sentence (Krismayani et al, 2021;Lin et al, 2017;Yusefi et al, 2015). Amongst those many types of English verb, the discussion in this study is focused on the use of speech act verbs, specifically the verb 'inform.'…”
Section: Introductionmentioning
confidence: 99%